2012
DOI: 10.1124/jpet.111.188953
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ΔFosB Immunoreactivity Induced by Vagal Nerve Stimulation with That Caused by Pharmacologically Diverse Antidepressants

Abstract: Vagal nerve stimulation (VNS) has been approved for treatment of refractory depression. However, there have been few, if any, studies directly comparing the effects produced by VNS in animals with those caused by antidepressants, particularly using clinically relevant stimulation parameters in nonanesthetized animals. In this study, ⌬FosB immunohistochemistry was used to evaluate different brain regions activated by long-term administration of VNS. Effects of VNS were compared with those caused by sertraline o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Cunningham et al reported short‐term VNS (2 hours) in rats activated the nucleus of the solitary tract (NST), paraventricular nucleus of the hypothalamus, parabrachial nucleus (PBN), ventral bed nucleus of the stria terminalis, and locus coeruleus (LC) . Long‐term VNS (2‐3 weeks) activated all of the above regions as well as the cingulate cortex, ventrolateral periaqueductal gray (PAG), and dorsal raphe nucleus (DRN), reflecting the potential VNS action sites and a differential temporal response between noradrenergic and serotonergic neurons. Also, six‐day preemptive NST stimulation delayed epileptogenesis in cats .…”
Section: Recent Trials and Research On Vnsmentioning
confidence: 99%
“…Cunningham et al reported short‐term VNS (2 hours) in rats activated the nucleus of the solitary tract (NST), paraventricular nucleus of the hypothalamus, parabrachial nucleus (PBN), ventral bed nucleus of the stria terminalis, and locus coeruleus (LC) . Long‐term VNS (2‐3 weeks) activated all of the above regions as well as the cingulate cortex, ventrolateral periaqueductal gray (PAG), and dorsal raphe nucleus (DRN), reflecting the potential VNS action sites and a differential temporal response between noradrenergic and serotonergic neurons. Also, six‐day preemptive NST stimulation delayed epileptogenesis in cats .…”
Section: Recent Trials and Research On Vnsmentioning
confidence: 99%
“…51 In addition, acute VNS induced specific expression of nuclear fos gene that is an immediate early gene and a marker for neuronal activation in several forebrain structures, including the amygdala, cingulate cortex, hypothalamus, the brainstem, locus ceruleus, noradrenergic nuclei, and thalamus. 52 Chronic VNS significantly increased staining of ΔFosB (a marker of chronic neuronal activation) bilaterally in tractus solitarius, locus ceruleus, parabrachial nucleus, dorsal raphe nuclei, and in many cortical and limbic areas of brain including those involved in mood and cognition 53,54 . The VNS effects were more widespread than those caused by the antidepressants.…”
Section: Altered Neurotransmitter Levels and Cerebral Blood Flowmentioning
confidence: 99%
“…The VNS effects were more widespread than those caused by the antidepressants. 54 Locus ceruleus neurons impact Fos protein expression, suggesting a plastic mechanism for diminishing epileptogenesis. 55 These structures activated by the vagus may play an important role in the control of epilepsy, recognition memory, and control of arousal 47,56,57 .…”
Section: Altered Neurotransmitter Levels and Cerebral Blood Flowmentioning
confidence: 99%
“…Furthermore, VNS in model of depression increased neurogenesis and enhanced neural activity in many brain areas involving cognition2223. Moreover, VNS in normal rats has been shown to modulate neuronal plasticity and increased dendritic complexity24.…”
mentioning
confidence: 99%